The electrochemical reduction of a flexible Mn(ii) salen-based metal–organic framework. Issue 37 (9th September 2021) - Solomon, Marcello B.; Hua, Carol; Chan, Bun; Church, Tamara L.; Cohen, Seth M.; Kubiak, Clifford P.; Jolliffe, Katrina A.; D'Alessandro, Deanna M.
Abstract : A salen-based MOF is reported that is stable to desolvation and exhibits a crystalline-to-amorphous transition. The framework is stable to a one-electron reduction, which is characterised spectroelectrochemically and using computational calculations. Abstract : A new metal–organic framework (MOF) containing a Mn(ii ) salen complex (BET surface area = 967 ± 6 m 2 g −1 ) undergoes a reversible crystalline-to-amorphous transformation. Experimental studies and computational calculations show that the MOF is stable to a one-electron reduction at more anodic potentials than the corresponding discrete complex.